Pemberdayaan Kelompok Tani Melalui Penerapan Teknologi Mesin Pengupas Kulit Kopi untuk Meningkatkan Efisiensi Produksi di Desa Boangmanalu Kabupaten Pakpak Bharat - Ulgari, Siti; Siahaan, Sabda Dian Nurani; Silaban, Saronom; Boangmanalu, Eka Putra Dairi; Sibarani, Choms Gary Ganda Tua; Lukman, Mena Fadilia; Atika, Liana (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2025)
This community partnership program (PKM) aims to improve production efficiency, work capacity, and farmers’ skills in coffee bean processing through the application of appropriate technology within the Mborgang Farmer Group in Boangmanalu Village, Pakpak Bharat Regency. The implementation methods consisted of socialization, training, technology application, and continuous mentoring. The evaluation instruments included field observation sheets and interviews, which were analyzed descriptively using both qualitative and quantitative approaches. The results of the program showed a significant increase in time efficiency and production capacity, from approximately 12 kg per hour to 100 kg per hour. In addition, farmers demonstrated improved understanding and skills in operating the machines, which had a positive impact on work effectiveness and time efficiency.